Doubling diet fat on sugar ratio in children with mitochondrial OXPHOS disorders: Effects of a randomized trial on resting energy expenditure, diet induced thermogenesis and body composition. Issue 6 (December 2016) - Béghin, Laurent; Coopman, Stéphanie; Schiff, Manuel; Vamecq, Joseph; Mention-Mulliez, Karine; Hankard, Régis; Cuisset, Jean-Marie; Ogier, Hélène; Gottrand, Frédéric; Dobbelaere, Dries
Summary: Background & aims: Mitochondrial OXPHOS disorders (MODs) affect one or several complexes of respiratory chain oxidative phosphorylation. An increased fat/low-carbohydrate ratio of the diet was recommended for treating MODs without, however, evaluating its potential benefits through changes in the respective contributions of cell pathways (glycolysis, fatty acid oxidation) initiating energy production. Therefore, the objective of the present work was to compare Resting Energy Expenditure (REE) under basal diet (BD) and challenging diet (CD) in which fat on sugar content ratio was doubled. Diet-induced thermogenesis (DIT) and body compositions were also compared. Energetic vs regulatory aspects of increasing fat contribution to total nutritional energy input were essentially addressed through measures primarily aiming at modifying total fat amounts and not the types of fats in designed diets. Methods: In this randomized cross-over study, BD contained 10% proteins/30% lipids/60% carbohydrates (fat on sugar ratio = 0.5) and was the imposed diet at baseline. CD contained 10% proteins/45% lipids/45% carbohydrates (fat on sugar ratio = 1). Main and second evaluation criteria measured by indirect calorimetry (QUARK RMR ®, Cosmed, Pavona; Italy) were REE and DIT, respectively. Thirty four MOD patients were included; 22 (mean age 13.2 ± 4.7 years, 50% female; BMI 16.9 ± 4.2 kg/m 2 ) were evaluated for REE, and 12 (mean age 13.8 ± 4.8 years, 60% female; BMI 17.4 ± 4.6 kg/m 2 ) also for DIT. OXPHOS complex deficiency repartition in 22 analysed patients was 55% for complex I, 9% for complex III, 27% for complex IV and 9% for other proteins. Results: Neither carry-over nor period effects were detected (p = 0.878; ANOVA for repeated measures). REE was similar between BD vs CD (1148.8 ± 301.7 vs 1156.1 ± 278.8 kcal/day; p = 0.942) as well as DIT (peak DIT 260 vs 265 kcal/day; p = 0.842) and body composition (21.9 ± 13.0 vs 21.6 ± 13.3% of fat mass; p = 0.810). Conclusion: Doubling diet fat on sugar ratio does not appear to improve, per se, energetic status and body composition of patients with MODs.